LC ESI-MS and FT-IR Analysis of Dendrophthoe pentandra L. Miq Leaf Methanolic Extracts to Identify Compounds with Progesterone-Like Effects - Lazuardi, M.; Hermanto, B. (Pakistan Journal of Nutrition, 2016)
An earlier study found that progesterone hormone levels in adult female rats increased by nearly two-fold relative to usual levels following intramuscular injection (w/v, 100 mg/kg body weight for four days (s.d.d.)) of methanol extracts of Dendrophthoe petandra L. Miq (common name Benalu duku) leaves. This result suggests that Benalu duku contains pregnane derivative steroids that have carbon bonding at positions 1 and 21. Here we examined the specificity and pharmacodynamics of active substances with progesterone-like effects in crude methanol extracts made from Benalu duku leaves. Pulverized Benalu duku leaves (400 g) were extracted with 2 L analytical grade methanol at 20°C for 72 h using a shaker maceration method. The semi-solid crude extract was dried under vacuum and exposed to UV light prior to spectroscopic analysis. FT-IR and LC ESI MS analysis detected active substances having a pregnane derivative chemical structure with progesterone, medroxy progesterone acetate, megestrol acetate and dydrogesterone present at distributions of about 30, 66, 3 and 1%.